From “Honest Connie” to “Rockpile Rink”: The Political Rise and Fall of Cornelius Rink in 1930s Regina - Brennan, J. (Urban History Review / Revue d'histoire urbaine, 2012)
Little has been written about Depression-era municipal politics in Canada. This article considers Regina’s experience by examining the turbulent career of its most successful populist politician, Cornelius Rink. He was twice elected mayor (in 1933 and 1934) on the strength of his appeal among Regina’s immigrant and working-class voters. Then in 1935, in the aftermath of the On-to-Ottawa Trekkers’ sojourn in the city and a riot there on 1 July, social democrats and trade unionists with an attractive platform and a more effective organization managed to unseat Rink with the votes of many of those same immigrant and working-class Reginans. Cornelius Rink was Regina’s first populist mayor, but as it turned out he would be its only one.